103 Insurance Status Predicts Patient Safety and Care Quality in the Lumbar Spine Fusion Population. (August 2016) - Tanenbaum, Joseph E; Alentado, Vincent J.; Miller, Jacob A.; Lubelski, Daniel; Benzel, Edward C.; Mroz, Thomas E.
Abstract : INTRODUCTION: Lumbar fusion is a common and costly procedure in the United States. Reimbursement for surgical procedures is increasingly tied to care quality and patient safety as part of value-based reimbursement programs. The incidence of adverse quality events among lumbar fusion patients is unknown using the definition of care quality (named patient safety indicators [PSI]) utilized by the Centers for Medicare and Medicaid Services (CMS). Disparities in PSI incidence have been observed across insurance groups in other surgical spine populations. The association between insurance status and the incidence of adverse care quality as measured by PSI is unknown in lumbar fusion patients. METHODS: Nationwide inpatient sample (NIS) data were queried for all cases of inpatient lumbar fusion from 1998 to 2011. Patients were excluded if "other" or "missing" was listed for primary insurance status and if age was less than 18 years. Incidence of adverse patient safety events (PSI) was determined using publicly available lists of International Classification of Diseases, Ninth Revision, Clinical Modification diagnosis codes. Logistic regression models were used to determine the association between primary payer status (Medicaid/self-pay relative to private insurance) and the incidence of PSI. RESULTS: From 1998 to 2011, 564 930 lumbar fusion procedures were recorded in the NIS. After applying inclusion criteria, 461 417 remained for analysis. The national incidence of PSI was calculated to be 2445 per 100 000 patient-years of observation, or approximately 2.5% After adjusting for patient demographics and hospital characteristics, Medicaid/self-pay patients had significantly greater odds of experiencing one or more PSI during the inpatient episode relative to privately insured patients (odds ratio, 1.16; 95% confidence interval, 1.07-1.27). CONCLUSION: Among patients undergoing inpatient lumbar fusion, insurance status predicts adverse health care quality events used to determine hospital reimbursement by CMS. The source of this disparity must be studied to improve the quality of care delivered to vulnerable patient populations.